A randomized controlled comparison of three modes of ventilation during cardiopulmonary bypass on oxygenation in pediatric patients with pulmonary hypertension undergoing congenital heart surgeries. Issue 1 (31st December 2022) - Gado, Ahmed Ali; Hefnawy, Salwa Mohamed; Abdelrahim, Ashraf M; Alberry, Mostafa Abdel Wahab Abdel Aziz; Madkour, Mai A. El Fattah
ABSTRACT: Background: Several studies have attempted to improve post bypass oxygenation, decrease extravascular total lung water volume, utilizing continuous positive airway pressure (CPAP) and high-frequency ventilation (HFV) during cardiopulmonary bypass (CPB). Aims: To assess the influence of various ventilation modes during CPB on direct pulmonary artery systolic pressure and post bypass oxygenation in pediatric patients with moderate to severe pulmonary hypertension undergoing corrective cardiac surgeries. Methods: Included in the study were 24 patients aged 4 months to 6 years, suffering from moderate to severe pulmonary hypertension, undergoing elective corrective cardiac surgeries for atrial septal defect (ASD) or ventricular septal defect (VSD) or atrioventricular canal defects (AVC) (ASA II and III). Group A patients ( n = 8) received high-frequency positive pressure ventilation during cardiopulmonary bypass, Group B patients ( n = 8) received continuous positive, while group C patients ( n = 8) disconnected from the ventilation (passive deflation) (control group). Results: There was no statistically significant difference regarding the pulmonary artery systolic pressure (PASP) and pulmonary artery systolic pressure to systemic systolic blood pressure (PASP/SSBP Ratio) at t1, t2, and t3 between the three groups. Conclusion: After cadiopulmonary bypass, no significant changes in pulmonary artery pressure was observed in pediatric patients, regardless of the ventilation mode utilized during cardiopulmonary bypass. Conversely, the pulmonary outcomes; delivered Oxygen (DA-aO2), arterial oxygen tension (paO2) and paO2/FiO2 (p/f ratio) and lung ultrasound (LUS) were significantly improved when comparing continuous positive airway pressure (CPAP) with high frequency positive pressure ventilation (HFPPV) and passive deflation during cardiopulmonary bypass.